The implementation of a Web-based Learning Environment concerning teachers’ collaboration in the area of Fluids - Paraskevas, A.; Psillos, D. (Proceedings of the International Conference on Networked Learning, 2008)
In our work we developed and implemented a specially developed web-based distance learning course, addressed to in service primary teachers in Greece in the area of fluids. The course aims at enhancing participants’ understanding of fluids and as well as their collaboration towards producing teaching learning materials for their pupils. Fluids is taught in primary schools, in several countries including Greece, in which pupils and teachers have alternative views and difficulties, in understanding basic ideas concerning pressure and buoyancy. We implemented a specific strategy, in order to promote asynchronous collaboration among participants and evaluated results by using Murphy`s quantitative content analysis model. During recent years, in the area of higher education, a great number of applications have used Web-based learning environments, in order to support distance learning courses and computer supported collaborative approaches, in learning and problem solving, in several areas. Computer-mediated communication can facilitate collaborative learning strategies and approaches, thus providing opportunities for virtual communities of learners to collaborate in ways that lead to shared understanding. Evaluating on-line collaborative learning interactions is a complex task due to the variety of elements and factors that take place and intervene, in the way a group of participants comes together to collaborate, in order to achieve a learning goal. In this context, we developed a web based teaching strategy aiming at enhancing participants’ understanding of fluids and as well as their collaboration towards producing teaching learning materials for their pupils. In the present study, we report on the strategy and the collaborative activities of participating teachers. The sample of our study consisted of twenty four, (24), experienced primary teachers, who attended a two years in service program at the Department of Primary Education, University of Thessaloniki. In developing the course, first software for the Web based learning environment implementation was chosen and the open source software B.S.C.W. (Basic Support for Collaborative Work), has been chosen, because it is free for academic use,(http://bscw.gmd.de/ ). Second specially developed materials in the area of fluids were digitized and uploaded to the environment. Third based on data from two pilot studies, we designed a special mixed strategy in order to enhance teacher’s collaboration. In order to identify collaboration possibilities, among teachers, we carried out quantitative content analysis of their written dialogues, using the widely applied model of Murphy. It is characteristic that one hundred fifty seven messages (157), found in the phases "co-construct shared perspectives" and "building shared goals", constitute the two thirds of the total messages. This number seems to point out that participants, despite the high complexity of the scientific topic, successfully managed to co-construct shared perspectives and building shared goals, taking under consideration content knowledge. It is possible that enhancement of their understandings of pressure and buoyancy supplied before the collaborative phase of the strategy facilitated participants to reach the higher levels in Murphy’s’ model. As a matter of fact achieving such levels in web based collaborative activities may not be taken for granted, (Murphy, 2004). In other words we consider that if content knowledge was insufficient, we might found postings only from the first two phases of Murphy`s model, (social interaction & articulating individual perspectives), perhaps as monologues. The production of twelve shared artefacts from all participants, considered as identification and completion of collaboration. That is also a key element therefore all participants reached that phase, without any withdraws. We consider that participants were helped to achieve such goal by being specifically guided on how to collaborate instead of being left to proceed without instruction in a learning situation for which they had little prior experience.